KEBERLANJUTAN PENGELOLAAN EKOSISTEM MANGROVE PULAU MANTEHAGE, KECAMATAN WORI, KABUPATEN MINAHASA UTARA PROVINSI SULAWESI UTARA - Schaduw, Joshian Nicolas William (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2015)
This study aimed to analyze the sustainability of mangrove ecosystem management in one small island located in the area of Bunaken National Park. Mantehage islands included in the township administration area Wori, North Minahasa Regency, North Sulawesi. This study will examine the sustainability of mangrove ecosystem management on the dimension of ecological, socio-economic, and institutional. The data used are primary and secondary analyzes that are used in this study is the Multidimensional scaling. The results obtained are sustainability Status Mantehage Island mangrove ecosystem management included in either category, but one of the three dimensions of the object of study has a low value that the ecological dimension. Environmental degradation caused by anthropogenic activities and the nature of this dimension will affect the future, so that special attention is needed for improved its environmental capacity, especially in the mangrove ecosystem.